2016
DOI: 10.7150/jgen.16885
|View full text |Cite
|
Sign up to set email alerts
|

De novo Assembly and Analysis of the Chilean Pencil Catfish Trichomycterus areolatus Transcriptome

Abstract: Trichomycterus areolatus is an endemic species of pencil catfish that inhabits the riffles and rapids of many freshwater ecosystems of Chile. Despite its unique adaptation to Chile's high gradient watersheds and therefore potential application in the investigation of ecosystem integrity and environmental contamination, relatively little is known regarding the molecular biology of this environmental sentinel. Here, we detail the assembly of the Trichomycterus areolatus transcriptome, a molecular resource for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…Thus, studies on molecular-level understanding of sh physiology in response to biotic and abiotic stressors are required. The advances in NGS technologies and computational tools have been helpful in the whole genome and transcriptome sequencing of several species for a better understanding of their biology and the changes that occur due to climate change (Chatchaiphan et al, 2017, Schulze et al, 2016. Several studies in teleost depicted that temperature affects sh physiology and they cope with that via adaptation (Akbarzadeh et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, studies on molecular-level understanding of sh physiology in response to biotic and abiotic stressors are required. The advances in NGS technologies and computational tools have been helpful in the whole genome and transcriptome sequencing of several species for a better understanding of their biology and the changes that occur due to climate change (Chatchaiphan et al, 2017, Schulze et al, 2016. Several studies in teleost depicted that temperature affects sh physiology and they cope with that via adaptation (Akbarzadeh et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Lu et al [ 83 ] reported over-expression of this gene in the brains of male catfish ( Pelteobagrus fulvidraco ), indicating that the differential expression of spaca4 in the two sexes may provide an informative tool for sexing juvenile arapaima. The spaca4 gene was also found to be up-regulated in analyses of the transcriptomes of two fish, Trichomycterus areolatus [ 84 ], based on whole-body samples, and Ictalurus punctatus [ 85 ], focusing on the testicles. While this gene is up-regulated in the males of many different organisms, it was also expressed in the liver libraries of both the male and female arapaima, which indicates that the lack of contigs in the skin of the females does not necessarily mean that the gene was not expressed in this tissue, but rather that there may have been a reduced level of recuperation of the reads from this library.…”
Section: Discussionmentioning
confidence: 99%
“…Bioinformatics analysis of metatranscriptomics data. The raw fastq files of each animal were analyzed with our metatranscriptomic analysis workflow, built on several previous studies (Gaur et al, 2016;Haas et al, 2013;Livernois et al, 2016;Mora-Ortiz et al, 2016;Schulze et al, 2016). The process is briefly described as follows.…”
Section: Methodsmentioning
confidence: 99%